Optimization of substrate formulation for Hericium erinaceus by replacing wood by straw and their effect on enzyme activities - Lu, Zhu; Liu, Lingyun; Ren, Ziming; Hu, Shuang; Wang, Yue; Ji, Shujuan; Wang, Xu; Du, Zhongwei; Liu, Yanni; Yang, Yang; Yu, Yanshen (Frontiers in Plant Science, 2024)
Introduction China is rich in straw resources. The utilization of straw in the cultivation of edible fungi partially resolves the resource conflicts between mushroom cultivation and forest industry and also contributes to environmental protection. Methods In this study, based on the technology of replacing wood by grass, the straw formula for mycelial culture of Hericium erinaceus was optimized with Simplex-lattice method commonly used in mixture design. By measuring the growth rate and the activity of lignocellulose degrading enzymes of mycelia in different formulations, and further combining with model optimization, the optimal formulation was screened and validated for mushroom cultivation. Results In the experiments, different kinds of straw used as the main material showed interaction effects, further affecting the growth rate of mycelia and the activities of laccase, cellulase, and neutral xylanase. The screened optimal formula was composed of 16.3% rice straw, 59.7% cob, 20.0% wheat bran, 2.0% gypsum, 1.0% sucrose, and 1.0% calcium superphosphate. In the mushroom cultivation, 445.69 g of fresh mushroom were obtained and the biological efficiency reached 89.14%. The growth period of the first mushroom was shortened by 7-9 days. Some nutritional components of fruiting bodies, such as crude fats (6.10%), crude proteins (152.02 g/kg), K (19.71 g/kg), P (2.48 g/kg), and Se (6.06 g/kg), were significantly higher than those of the control formula. Discussion These above indicators indicated that the screened formula could be applied in the high-yield and high-quality cultivation of H. erinaceus. Our study lays the foundation for expanding cultivation and strains improvement of H. erinaceus, and is conducive in promoting the rapid development of H. erinaceus industry.